2010
DOI: 10.3390/toxins2112622
|View full text |Cite
|
Sign up to set email alerts
|

Tetanus Toxin C-Fragment: The Courier and the Cure?

Abstract: In many neurological disorders strategies for a specific delivery of a biological activity from the periphery to the central nervous system (CNS) remains a considerable challenge for successful therapy. Reporter assays have established that the non-toxic C-fragment of tetanus toxin (TTC), provided either as protein or encoded by non-viral naked DNA plasmid, binds pre-synaptic motor neuron terminals and can facilitate the retrograde axonal transport of desired therapeutic molecules to the CNS. Alleviated sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 121 publications
(170 reference statements)
0
36
0
Order By: Relevance
“…This was achieved by recombinant expression of the latter as proteins fused to CS, which assisted sensitive detection of the resultant probes with biotinylated reporter enzymes and fluors. Whilst others have reported that full-length TeTx (or toxoid) binds nerves more avidly than fragments of its HC (Weller et al 1986;Fishman et al 1999), and is transported more effectively along axons to spinal cord neurons (Weller et al 1986), these findings are controversial because TeTx C-terminal fragments also target and invade nerves and undergo retrograde axonal transport (Fishman 2009;Toivonen et al 2010). So far, the inferior neurotropism and axonal trafficking of TeTx fragments were attributed to their partial denaturation owing to production methods, or separation from TeTx through proteolytic cleavage (Weller et al 1986).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This was achieved by recombinant expression of the latter as proteins fused to CS, which assisted sensitive detection of the resultant probes with biotinylated reporter enzymes and fluors. Whilst others have reported that full-length TeTx (or toxoid) binds nerves more avidly than fragments of its HC (Weller et al 1986;Fishman et al 1999), and is transported more effectively along axons to spinal cord neurons (Weller et al 1986), these findings are controversial because TeTx C-terminal fragments also target and invade nerves and undergo retrograde axonal transport (Fishman 2009;Toivonen et al 2010). So far, the inferior neurotropism and axonal trafficking of TeTx fragments were attributed to their partial denaturation owing to production methods, or separation from TeTx through proteolytic cleavage (Weller et al 1986).…”
Section: Discussionmentioning
confidence: 97%
“…The remarkable capability of TeTx to target nerve terminals at the periphery and undergo retro-axonal transport to central neurons, along with its direct relevance to the patho-biology and clinical manifestation of the spastic neuroparalytic condition, tetanus, have generated much interest due to its potential as a therapeutic carrier (Fishman 2009;Toivonen et al 2010). In fact, TeTx or its H C have been shown to endow enhanced neurotropism to an array of attached proteins or viral vectors (Beaude et al 1990;Fishman et al 1990;Dobrenis et al 1992;Coen et al 1997;Figueiredo et al 1997;Francis et al 1997;O'Leary et al 2013).…”
Section: Introductionmentioning
confidence: 97%
“…6,7 Indeed, its potential as a therapeutic carrier has already been explored as a coupling agent to mediate the transport of proteins or viral vectors to neurons. [8][9][10] When functionalized with the pegylated HC fragment, the developed thiolated PEI-based nanoparticles (PEISH-HC) showed the ability to transfect primary cultures of dissociated dorsal root ganglia (DRG) neurons in a specific fashion. 5 Here, we aimed to evaluate the in vivo performance of these targeted nanoparticles, assessing their capacity to retrogradely access and transfect lumbar DRG neurons after a peripheral and minimally invasive administration in the animal's footpad.…”
mentioning
confidence: 99%
“…Tetanus toxin is a neurotoxin produced by Clostridium tetani, an anaerobic bacterium whose spores are commonly found in soil and animal waste. This toxin affects the nervous system and causes generalized muscle contractions, called titanic spasms [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…As an example, several proteins conjugated to TTC that have been used to study neuronal internalization in vitro and in vivo are horseradish peroxidise (HPRT), glucose oxidase (GO), green fluorescent protein (GFP), β -Nacetylhexosaminidase-A (HEXA), superoxide dismutase 1 (SOD1), survival motor neuron 1 (SMN1), cardiotrophin-1 (CT1), B-cell lymphomaextra large (Bcl-xL), IGF-1, glial derived neurotrophic factor (GDNF) and brain derived neurotrophic factor (BDNF) [17]. More recently, a novel multi-component nanoparticle system using polyethylene imine (PEI) has been evaluated to elicit the expression of BDNF in neuronal cell lines [44].…”
Section: Introductionmentioning
confidence: 99%